FACTORS INFLUENCING THE INTENTION TO CONSUME HALAL FOOD AND BEVERAGE PRODUCTS THROUGH ONLINE PLATFORMS: EVIDENCE FROM MUSLIM MILLENNIALS IN KENDARI CITY - Muljibir Rahman; Ardian Dwi Rahma; Abdul Wahid Mongkito; Trisno Wardy Putra (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to examine the factors influencing awareness, attitudes, and intention to consume halal food and beverage products through online ordering applications, particularly among Muslim millennials in Kendari City. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 96 Muslim millennial respondents in Kendari City, selected using purposive sampling. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to assess the relationships among religiosity, product knowledge, awareness, attitude, and intention. The results indicate that awareness and attitude have a significant positive effect on the intention to consume halal products online. Religiosity and product knowledge do not directly influence intention. However, both religiosity and product knowledge significantly affect awareness. Furthermore, religiosity and awareness significantly influence attitudes, while product knowledge does not show a significant effect on attitudes. The findings suggest that halal certification authorities, online food ordering platforms, and halal food vendors should strengthen consumer awareness by improving the visibility of halal certification, providing transparent product information, and promoting halal literacy through digital channels. Enhancing consumers’ awareness and attitudes toward halal products may increase their intention to purchase halal food and beverages online. However, the study is limited by its relatively small sample size of 96 respondents and its focus on Muslim millennials in Kendari City, which may limit the generalizability of the findings to other populations and geographical contexts. This study provides empirical insights into the behavioral determinants of halal consumption in the context of digital platforms, highlighting the mediating roles of awareness and attitude. It contributes to the growing literature on halal consumer behavior by focusing on Muslim millennials and the use of online food ordering applications, particularly in a regional Indonesian context.